Performance of the Quantitative Latex Immunoturbidimetric D-dimer Assay for the Diagnosis of Acute Pulmonary Embolism at Rafik Hariri University Hospital - Rida Salman; Mira Alsheikh; Rim Ismail (Shahrekord University of Medical Sciences, 2020)
Background and aims: The diagnostic workup for pulmonary embolism (PE) includes D-dimer assay and computed tomographic angiography. Several D-dimer assays have been approved for PE diagnosis with different sensitivity and specificity. We aimed to study the sensitivity and specificity of the quantitative latex agglutination D-dimer assay used in a referral teaching hospital in Lebanon for the diagnosis of acute PE. Methods: Using a retrospective chart review, we studied 300 patients who had D-dimer test at Rafik Hariri University Hospital in the period between January 1, 2012 and December 31, 2013. Accordingly, 93 patients had a CT angiography after being suspected to have acute PE. A statistical table 2*2 was used to compare the results of CT angiography and D-dimer test. Results: Thirteen patients (13.97%) had PE and 60 patients (64.51%) had positive D-dimer test. Quantitative latex agglutination D-dimer assay had a sensitivity of 69%, specificity of 36%, and negative predictive value of 88%. False positive ratio was also 64%. Moreover, the receiver operating characteristic (ROC) curve was obtained with an area under the curve measuring 0.527. Conclusion: Quantitative latex agglutination D-dimer assay has a high negative predictive value; thus, it can exclude a PE diagnosis if it is associated with low clinical pretest probability.